Optimizing fertilizer use for sustainable food systems: an evaluation of integrated water-fertilizer system adoption among cotton farmers in China - Yuan, Yinghui; Wang, Changyi; Zai, Xueming; Song, Yulan; Zhang, Xiaoheng (Frontiers in Sustainable Food Systems, 2023)
In the face of escalating apprehensions surroundingAmid growing concerns for food security, the sustainability ofsustainable food systems, and food quality, the ingenuity of resource management strategies becomes paramountinnovative resource management strategies are of paramount importance. A key component within these strategies is the enhancement of chemical fertilizer utilization, an element that bears significant weight on agricultural yields and the preservation of our environment..A pivotal element in this context is the optimization of chemical fertilizer use, which directly influences both agricultural productivity and environmental sustainability. The emergence of Integrated Water-Fertilizer Systems (IWFS) thus presents a significant innovation in boosting the efficiency of chemical fertilizer usage, necessitating in-depth examination.Integrated Water-Fertilizer Systems (IWFS) emerge as a crucial innovation in enhancing chemical fertilizer use efficiency, warranting comprehensive evaluation. UtilizingEmploying a rigorous analytical framework that combines meta-frontier production function andwith a Two-Stage Residual Inclusion model, this study delves into the multi-dimensionalassesses the multifaceted impacts of IWFS adoption on fertilizer use efficiency among cotton farmers growers in Xinjiang, China. Empirical evidence demonstrates that those who have adopted IWFS achieve a fertilizer use efficiency score of 0.452, markedly outstripping the mean score of 0.382 among non-adopters.Empirical findings indicate that IWFS adopters attain a fertilizer use efficiency score of 0.452, significantly surpassing the average score of 0.382 among non-adopters. Intriguingly, efficiency increases proportionately with the size of the farmNotably, efficiency gains are found to scale with farm size, hinting at a sophisticated interplay between the adoption of technology and operational parameters revealing a complex interplay between technological adoption and operational dimensions. The research further unveils additional benefits including augmented cotton yields and diminished also reveals ancillary benefits, such as increased cotton yields and reduced labor inputs among adopters. These multifacetedcomplex outcomes bear significanthave profound policy implications, highlightingunderlining the transformative potential of IWFS in promoting advancing sustainable food systems, bolstering food security, and enhancing food quality.